Where and when to pray? Optimal mass planning and efficient resource allocation in the church - Alexander Martin; Martin Weibelzahl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2014)
We will present a theoretical model for an integrated planning of Eucharistic masses and Liturgies of the Word assuming different priests, assistant priests and lay persons. This all-integer vector optimization problem can be seen as an economic, spacial and inter-temporal resource allocation problem taking the challenges in the context of parish clusters into account. Having provided some theoretical insights into the mass planning problem, numerical results show the relevance of our model for an efficient decision-making in religious practice. We demonstrate that innovative team work arrangements in the church can substantially improve the efficiency, fairness and acceptance of mass allocations.
Keywords: C61; D63; L31; M54; 330; Allocation; Resources; Church; Job Design and Cooperation; Labor and Personnel Management; Normative Criteria; Optimization Models